Genetic structure in neotropical birds with different tolerance to urbanization - Rodríguez Bardía, Mauricio Alejandro (2022)
Gene flow in birds can be affected by urbanization depending on natural history traits and adaptability to habitat change. Contrasting results can be expected when comparing species with opposite resilience to urbanization. In this study, we assessed genetic diversity and structure for two bird species, the urban avoider white-eared ground-sparrow, Melozone leucotis, and the urban dweller house wren Troglodytes aedon. We used seven microsatellite loci and sampled five locations with differing levels of urbanization in Costa Rica. We found considerably higher genetic structure in whiteeared ground-sparrows than in house wrens. Circuit theory analyses proved a higher isolation from urban resistance for the white-eared ground-sparrow than for house wrens. These results support that urbanization is a significant barrier for gene flow in urban avoiders, in contrast to urban dweller species that showed little to no impact. Differences could be attributed to a higher plasticity in habitat and nesting site preferences in the house wren, and significant dispersal limitation for the white-eared ground-sparrow. These results emphasize the need for conservation strategies towards white-eared ground-sparrows and other urban avoider species whose habitat and connectivity have been reduced by the recent urban expansion.